Integrating the English Language Arts Common Core State Standards into Physical Education - James, Alisa R.; Bullock, Kerri (Journal of physical education, recreation & dance, 2015)
Physical education teachers are expected to implement the English language arts (ELA) Common Core State Standards (CCSS) in their instruction. This has proved to be challenging for many physical educators. The purpose of this article is to provide developmentally appropriate examples of how to incorporate the ELA CCSS into physical education, while at the same time aligning the CCSS with the new national physical education content standards and grade-level outcomes.